Pengaruh Produksi, Harga, Kurs dan Tarif 0% Terhadap Ekspor CPO Indonesia dalam Skema ACFTA - Putra, I Dewa Gede Darma; Sudirman, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 3, No. 9, September 2014 (pp. 395-430), 2014)
Crude Palm Oil ( CPO ) as the main export commodity for Indonesia has contributed greatly to the economy of the agricultural sector in the agreement Indonesia.Dimasukkannya ASEAN - China Free Trade Area ( ACFTA ) means the Indonesian CPO should be ready to compete freely on Indonesian CPO is ACFTA.Ekspor the highest in the world , Indonesia must therefore be defended in the ACFTA which is one of the gates to the liberalization of the economy . This study aims to determine the effect of production , price , exchange rate , and the rate of 0 % on Indonesian CPO exports in ACFTA scheme in the period 2001-2012 . The data in this study come from the UN trade database , Statistics Indonesia , the Malaysian Palm Oil Board ( MPOB ) and literature - literature terkait.Teknik analysis used in this study is ordinary least square analysis techniques. Berdasarkan results of the analysis found that the production rate 0 % positive and significant impact on Indonesian CPO exports in the period 2001-2012 ACFTA scheme, while the price and the dollar exchange rate has no effect Indonesian CPO exports in the period 2001-2012 ACFTA scheme.
Keywords: Indonesian CPO exports; ACFTA; Production; Price; exchange rate; 0 % tariff